HAEMATOBIOCHEMICAL CHANGES IN DRUG INDUCED IMMUNOSUPPRESSED RABBITS. - Sumathy, R; Chattopadhyay, S; Batabyal, S; Pramanik, B K (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Haematobiochemical study was carried out in Dexamethasone and Cyclosporine A induced immunosuppressed rabbits. The results reveals that the drugs induced both negative and positive effect on haematological profile . Hemoglobin, TLC, protein, sodium and cortisol level significantly whereas glucose, cholesterol, potassium levels and alkaline phosphatase activity significantly increased .
Keywords: Dexamethasone; Cyclosporine A; Immuno-suppression; Haematobiochemical; Rabbits; INTRODUCTION